En bloc substitution of the Src homology region 2 domain activates the transforming potential of the c-Abl protein tyrosine kinase. - Muller, A J (1993)
Src homology region 2 (SH2) domains are present in many proteins involved in signal transduction. In nonreceptor protein tyrosine kinases the SH2 domain has been implicated in regulation of tyrosine kinase activity and in mediating interactions involved in downstream signaling. Different SH2 domains exhibit distinct binding specificities for both phosphotyrosine- and phosphoserine/phosphothreonine-containing proteins. We show that different SH2 domains are not functionally equivalent within the context of the c-ABL1b protooncogene. c-ABL1b, altered by replacement of its SH2 domain with the N-terminal SH2 domain of Ras GTPase-activating protein, exhibited activated transforming capability, caused intracellular tyrosine phosphorylation of p62, and was relocalized from nucleus to cytoplasm. This en bloc substitution apparently uncouples two distinct functions of the SH2 domain so that c-ABL escapes normal regulatory control while it retains the capability to elicit signals that promote transformation. The SH2 domain of the ARG protein tyrosine kinase, which shares high amino acid-sequence homology with the SH2 domain of ABL, was less effective in activating the oncogenic potential of c-ABL. The effects that the N-terminal SH2 domain of Ras GTPase-activating protein has in the context of c-ABL resemble the effects of deleting the SH3 domain. Thus, the SH2 and SH3 domains may have coordinate roles as regulatory control elements within the context of c-ABL.